Sejarah Perkembangan Tafsir - Faqih, Muhammad Wildan (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The activity of tafsir Qur'an has been started since the time of the Prophet Muhammad. and continues to develop from time to time, namely the period of the Prophet Muhammad. and his companions, the tabi'in period, and the modern period. By looking back at the history of the development of tafsir that has been alluded to, then of course each period and period of its development has its own uniqueness. This study aims to determine the history of the development of tafsir based on the three periods mentioned. The research method used is library research by collecting the required information from various reference sources such as books, notes, or research articles. The results of this study reveal that at the time of the Prophet Muhammad, the activity of tafsir the Qur'an continues to develop until it gives birth to various schools and methods of tafsir. At the time of the Companions, the Qur'an was interpreted using the riwayah method or sometimes ijtihad if a verse was not interpreted by the Prophet Muhammad. During the tabi'in period, the development of tafsir was marked by the emergence of schools of tafsir in Mecca, Medina, and Iraq. The development of commentary continues until the emergence of books of tafsir that occur in the tadwiin period or the period of codification of tafsir. After this period, the tafsir of the Qur'an entered the modern period which was marked by the emergence of a new method of interpreting the Qur'an, namely the maudhui method.